Elevated resting heart rate in heart transplant recipients: innocent bystander or adverse prognostic indicator?. (27th July 2015) - Wachter, S. Blake; McCandless, Sean P.; Gilbert, Edward M.; Stoddard, Gregory J.; Kfoury, Abdallah G.; Reid, Bruce B.; McKellar, Stephen H.; Nativi‐Nicolau, Jose; Saidi, Abdulfattah; Barney, Jacob; McCreath, Lauren; Koliopoulou, Antigone; et al.
Abstract: Background: The elevated baseline heart rate (HR) of a heart transplant recipient has previously been considered inconsequential. However, we hypothesized that a resting HR above 100 beats per minute (bpm) may be associated with morbidity and mortality. Methods: The U.T.A.H. Cardiac Transplant Program studied patients who received a heart transplant between 2000 and 2011. Outpatient HR values for each patient were averaged during the first year post‐transplant. The study cohort was divided into two groups: the tachycardic (TC) (HR >100 bpm) and the non‐TC group (HR ≤100 bpm) in which mortality, incidence of rejection, and cardiac allograft vasculopathy were compared. Results: Three hundred and ten patients were included as follows: 73 in the TC and 237 in the non‐TC group. The TC group had a higher risk of a 10‐yr all‐cause mortality (p = 0.004) and cardiovascular mortality (p = 0.044). After adjustment for donor and recipient characteristics in multivariable logistic regression analysis, the hazard ratio was 3.9, (p = 0.03, CI: 1.2–13.2) and 2.6 (p = 0.02, CI: 1.2–5.5) for cardiovascular mortality and all‐cause mortality, respectively. Conclusion: Heart transplant recipients with elevated resting HR appear to have higher mortality than those with lower resting HR. Whether pharmacologically lowering the HR would result in better outcomes warrants further investigation.